Efektivitas Direct Intruction dengan Involving Students in Self-and Peer Evaluation terhadap Hasil Belajar Ditinjau dari Gaya Kognitif - M. Zainudin; Dian Ratna Puspananda (Jurnal VARIDIKA, 2015)
The research objective is to proof 1). models of direct instruction by involving students in self-evaluation and peer learning can provide better results than direct instruction, 2). students having a field dependent cognitive style have better learning outcomes than field independent, 3). In each of the learning model, whether the student has a field dependent cognitive style have better learning outcomes than independent field, 4). In each of the cognitive style, whether the model of direct instruction by involving students in self-evaluation and peer learning can provide better results than direct instruction. The population of this study was all students of mathematics education of IKIP PGRI Bojonegoro, fourth semester, in the academic year of 2014/2015. The sample of this study was all students of the fourth semester students in class A with the total number of 32 students and class B as many as 32 students. The sampling technique in this study was cluster random sampling. Results of the study were 1) models of direct instruction by involving students in self-evaluation and peer learning can provide better results than direct instruction, 2) students who have cognitive style independent field has learning outcomes that are better than field-dependent, 3) In each of the learning model, students who have cognitive style independent fields have significantly a better learning outcomes than field dependent, 4) In each of the cognitive style, whether the model of direct instruction by involving students in self-evaluation and peer always provide better learning outcomes significantly than direct instruction.